MINDOMO: A DIGITAL MIND MAPPING IN ENHANCING STUDENTS’ WRITING SKILL - Rosdiana; Riski Mayusandra (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to find out the use of digital mind mapping through Mindomo application in enhancing students' writing skills focused on descriptive text in second grade at SMA Negeri 3 Teupah Selatan 2023/2024. The purposive sampling was used in this research which consists of 19 students. The instruments that is used to collect the data is pre-test and post-test. The result of the test shows that there is an increasing score of students from the pre-test to the post-test. The students' pre-test average score was 47.47 which were classified as poor grade, while the post-test score was higher than the pre-test average score of 78.15 which was categorized as an excelent category. Based on the explanation above, it can be concluded that the accepted hypothesis states that the use of digital mind mapping through the Mindomo application enhanced students’ ability in writing a descriptive text. Digital mind mapping (Mindomo aplication) allows students to brainstorm ideas collectively. This can be particularly useful for students to compose a descriptive text. The digital mind mapping through the mindomo application can be chosen as one of the effective technology to use in teaching writing in order to enhance students' writing skills particularly in descriptive text.